Evolutional background of dominance/submissivity in sex and bondage: the two strategies? - Jozifkova, Eva; Bartos, Ludek; Flegr, Jaroslav (Neuro endocrinology letters, 2012)
OBJECTIVES: We theorize that sexual arousal by dominance and submission may be connected to a reproduction strategy respecting a reached social dominance rank (a common reproduction strategy in socially living mammals), while the preference for "bondage" may be derived from an opportunistic strategy when being unable to compete for hierarchic rank (an alternative reproductive strategy that co-occurs frequently with the above-named main strategy). The answers to questions dealing with hierarchy in character should correlate exclusively with sexual arousal connected to any kind of expression of a hierarchy, but not with bondage. DESIGN AND SETTINGS: The data were obtained from young adults (157 males and 183 females aged 18-20, with mean 18.4 years) via questionnaires. RESULTS: Seven out of eight questions dealing with hierarchy correlated with sexual arousal by dominance and submission in men (Spearman's r=0.169-0.313; p<0.05 - p<0.001), two questions correlated with sexual arousal by dominance and submission in women (Spearman's r=0.32-0.166, p<0.001, p<0.05). THE MAIN FINDINGS: The questions dealing with hierarchy correlated with sexual arousal by dominance and submission while no answers correlated with bondage, neither in men nor in women. CONCLUSION: The preference for sexual arousal by dominance and submission may be connected to strategy respecting rank, while the preference for "bondage" may be derived from an opportunistic strategy that may be essential for possible partner problems solution. From the evolutionary biology point of view, these patterns of sadomasochistic sex appear as adaptive rather than as pathology.
Keywords: Surveys and Questionnaires; Adaptation, Psychological; Social Behavior; Humans; Sexual Behavior; Biological Evolution; Female; mladý dospělý; sociální chování; lidé; sociální hierarchie; průzkumy a dotazníky; dominance a subordinace; ženské pohlaví; Male; sadismus; Dominance-Subordination; biologická evoluce; Adolescent; adaptace psychologická; Young Adult; Hierarchy, Social; masochismus; Sadism; mužské pohlaví; Masochism; sexuální chování; mladiství